A combined genetic and physical map of the Streptomyces coelicolor A3(2) chromosome. - Kieser, H M (1992)
The restriction enzymes AseI (ATTAAT), DraI (TTTAAA), and SspI (AATATT) cut the Streptomyces coelicolor A3(2) chromosome into 17, 8, and 25 fragments separable by pulsed-field gel electrophoresis (PFGE). The sums of their lengths indicated that the chromosome consists of about 8 Mb of DNA, some 75% more than that of Escherichia coli K-12. A physical map of the chromosome was constructed for AseI and DraI, using single and double digests, linking clones, cross-hybridization of restriction fragments, and locations of genetically mapped genes, insertion sequences, prophages, and the integrated SCP1 and SLP1 plasmids on the physical map. The physical map was aligned with the previously established genetic map, revealing that the two long opposite quadrants of the genetic map that are almost devoid of markers (the silent regions at 3 o'clock and 9 o'clock) are indeed physically long rather than being hot spots for genetic exchange. They must therefore contain long stretches of DNA different in function from the remainder of the genome. Consistent with this conclusion are the locations of significant deletions in both of the silent regions. Of these, a 40-kb deletion in the 9 o'clock region accompanied or followed integration of the SCP1 linear plasmid to produce the NF fertility state. PFGE analysis of Streptomyces lividans 66, a close relative of S. coelicolor A3(2), was hampered by the previously described susceptibility of its DNA to degradation during electrophoresis. However, ZX7, a mutant derivative of S. lividans lacking the DNA modification responsible for this degradation, yielded good PFGE preparations. Not more than 7 of the 17 S. coelicolor AseI fragments could be shared by the S. lividans strain.